Isotopomics by isotope ratio monitoring by 13C nuclear magnetic resonance spectrometry on cutting agents in heroin: A new approach for illicit drugs trafficking route elucidation. Issue 4 (11th January 2020) - Joubert, Valentin; Trébuchet, Matéo; Mikic, Mariana; Silvestre, Virginie; Schiphorst, Anne‐Marie; Loquet, Denis; Stemmelen, Anaïs; Ladroue, Virginie; Besacier, Fabrice; Akoka, Serge; Remaud, Gérald S.
Abstract: In the battle against the illicit drugs market, methodologies have been developed by forensic laboratories to address the determination of the origin and dismantlement of the trafficking route for various target molecules such as heroin and cocaine. These drug profiling methods are not straightforward, especially when the target molecules are synthetic and very pure, resulting in poorly informative impurity profiles, e.g. new psychoactive substances and cutting agents. A tool based on the determination of intramolecular isotopic profiles has been developed to provide origin discrimination with a new way to profile seized cutting agents and heroin samples. Whereas stable isotope analyses by mass spectrometry give the bulk isotopic composition, nuclear magnetic resonance gives direct access to the position‐specific isotope content at natural abundance. This report shows how both 13 C NMR spectrometry and 13 C, 15 N MS might provide complementary and valuable information to link seized caffeine and paracetamol to their origin. Here, isotopic ratio monitoring by 13 C NMR (irm‐ 13 C NMR) offers additional benefits over irm‐MS in its capability to determine a detailed isotopic profile, leading to a better method to distinguish different caffeine and paracetamol batches. Abstract : Caffeine and paracetamol frequently appear together in heroin as cutting agents. Seizures of both products, adulterated heroin samples and reference materials were collected. Isotope ratio monitoring by mass spectrometry (carbon, nitrogen) and by nuclear magnetic resonance (carbon) were performed. The results shown here tend to demonstrate that these techniques can be used for sample comparison and batch linkage.